Successful Use of Posaconazole to Treat Invasive Cutaneous Fungal Infection in a Liver Transplant Patient on Sirolimus - Randah Dahlan; Ameen Patel; Shariq Haider (Canadian Journal of Infectious Diseases and Medical Microbiology)
Fungi are an important and common cause of cutaneous infections affecting solid organ transplant recipients. These infections can represent a primary site of infection with the potential for dissemination, or a manifestation of metastatic infection. The high morbidity and mortality associated with these infections necessitates urgent therapy with antifungal drugs; however, the interaction between these drugs and immunosuppressive therapies can be a major limitation because of drug toxicity. A case of soft tissue infection of the toe caused by Fusarium chlamydosporum and Candida guilliermondii in a liver transplant patient on sirolimus, who was successfully treated with the new antifungal agent posaconazole, is described. The pharmacokinetic interactions of sirolimus and the new triazoles, and their impact on treatment choices are briefly discussed.